2019
DOI: 10.1136/bmjpo-2019-000543
|View full text |Cite
|
Sign up to set email alerts
|

How are behavioural interventions delivered to children (5–11 years old): a systematic mapping review

Abstract: ContextBehavioural interventions are used to prevent, manage and treat a wide variety of conditions including obesity, diabetes, chronic pain, asthma and emotional difficulties. There has been inadequate attention to the delivery of behavioural interventions to younger children (5–11 years old).ObjectiveOur objectives were to describe the characteristics of behavioural interventions for children aged 5–11 years.Data sourcesWe searched five databases: CINAHL, EMBASE, PsycINFO, MEDLINE and Cochrane Library, from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 92 publications
0
7
0
Order By: Relevance
“…from the fields of asthma, cystic fibrosis, leukaemia, and congenital heart disease), and these indicate that explanations should be ‘concrete and focused on behavioural recommendations’ (Erickson et al, 2005). Using play, arts, games and storytelling methods may also be appropriate for educating this age group (Brigden et al, 2019). With regards to promoting self-management, only a minority of the children in this study were using strategies to monitor and regulate their activity levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…from the fields of asthma, cystic fibrosis, leukaemia, and congenital heart disease), and these indicate that explanations should be ‘concrete and focused on behavioural recommendations’ (Erickson et al, 2005). Using play, arts, games and storytelling methods may also be appropriate for educating this age group (Brigden et al, 2019). With regards to promoting self-management, only a minority of the children in this study were using strategies to monitor and regulate their activity levels.…”
Section: Discussionmentioning
confidence: 99%
“…With regards to promoting self-management, only a minority of the children in this study were using strategies to monitor and regulate their activity levels. However, children aged eight and upwards are typically involved in treatment (Brigden et al, 2019), they can be supported to self-manage their condition (e.g. self-administering insulin injections), and it is ethical and effective to involve children as much as possible (Alderson, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Open access using interactive methods (play, art, stories and games). 48 In addition, it was recommended to prepare children with disabilities for disasters with art and storytelling. 49 50 To prepare children for climate-related disasters in the time of pandemics, we recommend that: 1.…”
Section: Usamentioning
confidence: 99%
“… 47 Researchers in a systematic review found that programmes designed for children 5–11 years old should have some characteristics including the involvement of children’s parents, using behavioural modalities (rather than cognitive), and using interactive methods (play, art, stories and games). 48 In addition, it was recommended to prepare children with disabilities for disasters with art and storytelling. 49 50 …”
Section: Innovative Solutions For Preparing Children For Climate-relamentioning
confidence: 99%
“…There are examples of interventions for younger children which span clinical, educational and home settings (Brigden et al, 2019). Bringing health interventions into the school setting can improve health, psycho‐social and academic outcomes (Shaw & McCabe,2008).…”
Section: Introductionmentioning
confidence: 99%